Alterations of the cyclin D1/pRb/p16INK4A pathway in multiple myeloma - Krämer, Alwin; Schultheis, Beate; Bergmann, J.; Willer, Andreas; Hegenbart, Ute; Ho, Anthony Dick; Goldschmidt, Hartmut; Hehlmann, Rüdiger (Leukemia, 2002)
The retinoblastoma protein (pRb), p16INK4A, D-type cyclins, and their partners cyclin-dependent kinase (CDK) 4 and 6 constitute a G1 regulatory pathway commonly targeted in tumorigenesis. Several malignancies show a reciprocal correlation between genetic alterations of single members of the pRb pathway. Therefore, we determined the frequency of Rb deletions and cyclin D1 alterations by fluorescence in situ hybridization as well as 5′ CpG island hypermethylation of the p16INK4Agene using methylation-specific polymerase chain reaction in bone marrow mononuclear cells from 82 individuals with plasma cell disorders. Alterations in at least one of the components of the pathway were found in 75%. Cyclin D1 translocations or amplifications were detected in 14/82 (17.1%), Rb deletions at 13q14 in 23/82 (28%) of the cases, including three (3.6%) homozygous deletions. p16INK4A was hypermethylated in 33/57 (57.9%) of the samples. Further analysis revealed a highly significant correlation between cyclin D1 alterations and extramedullar or leukemic myeloma manifestations (P = 0.014; Fisher's test). Whereas Rb deletions seemed to occur alternatively to cyclin D1 alterations, no reciprocal correlation was found between p16INK4A hypermethylations and cyclin D1 or Rb locus aberrations. Cyclin D1 locus alterations and Rb deletions were associated with a significantly worse prognosis whereas p16INK4A hypermethylation had no impact on survival. We conclude that cyclin D1 and Rb aberrations seem to occur as alternative events in plasma cell malignancies and contribute to clinical course and prognosis. In contrast, although p16INK4A hypermethylation is frequent, inactivation of p16INK4A seems not to be involved in the pathogenesis of plasma cell disorders.
Gesehen am 14.12.2021
INK4A im Titel ist hochgestellt